A medical TPE material catheter material with high strength ultrasonic welding strength, and a preparation method and application thereof

CN123024218APending Publication Date: 2026-11-03GUANGZHOU HONSEA CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611201968.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing TPE materials cannot be effectively bonded to ABS materials. Ultrasonic welding strength is insufficient, posing a safety hazard of detachment. Furthermore, the adhesive has low volatility, making it easy to leave residues.

Method used

It uses components such as random copolymer polypropylene, hydrogenated styrene elastomer, maleic anhydride-grafted hydrogenated styrene elastomer, glycidyl methacrylate-grafted polyolefin elastomer, and thermoplastic polyurethane, and achieves a tight bond with ABS, PC, or nylon through ultrasonic welding to enhance adhesion.

Benefits of technology

It achieves high-strength ultrasonic welding, has high material safety, contains no plasticizers, meets the safety requirements of medical infusion catheters, has excellent welding strength, and is suitable for medical catheters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The application provides a medical TPE material catheter material with high ultrasonic welding strength and a preparation method and application thereof; the medical TPE material catheter material is prepared by using random copolymerized polypropylene, hydrogenated styrene elastomer, maleic anhydride grafted hydrogenated styrene elastomer, glycidyl methacrylate grafted polyolefin elastomer and thermoplastic polyurethane in cooperation, and is bonded with ABS, PC, nylon and other materials, does not need to use a solvent, can be welded together through ultrasonic waves, high temperature and the like, has excellent welding strength, and has a good industrial application prospect due to simple preparation process, easily obtained raw materials and moderate cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of medical polymer materials technology, and in particular relates to a medical TPE material catheter material with high ultrasonic welding strength, its preparation method and application. Background Technology

[0002] Medical infusion catheters require assembly with connectors. Previously, these catheters were made of PVC, which could be connected to ABS (acrylonitrile-butadiene-styrene) connectors using solvents. However, PVC infusion catheters have safety limitations in certain situations; for example, the plasticizers they contain may pose a hazard. Currently, the pediatric infusion field is gradually switching to TPE (tissue plasticizer) infusion catheters. TPE does not contain plasticizers, avoiding their harmful effects. However, TPE cannot be connected to ABS using the traditional solvents.

[0003] Currently, the adhesives used for joining TPE materials have low volatility and are more likely to leave residues. If TPE materials are joined using hot melt or ultrasonic welding, the joint strength is insufficient, posing a safety hazard of detachment. Summary of the Invention

[0004] This application provides medical TPE material catheters with high ultrasonic welding strength, their preparation method, and applications to solve the problems existing in related technologies. The technical solution is as follows: In a first aspect, embodiments of this application provide a medical TPE material catheter material with high ultrasonic welding strength, comprising the following components in parts by weight: 15-35 parts of random copolymer polypropylene; 40-60 parts of hydrogenated styrene elastomer; 3-10 parts of maleic anhydride-grafted hydrogenated styrene elastomer; 7-15 parts of glycidyl methacrylate-grafted polyolefin elastomer; 3 to 8 parts of thermoplastic polyurethane.

[0005] Styrene-based elastomers are conventional thermoplastic elastomers with poor processability and high cost. This application uses hydrogenated styrene-based elastomers as the main component, combined with random copolymer polypropylene. Polypropylene reduces the amount of styrene-based elastomer used, lowering costs, and provides skeletal support, thus improving the material's processability and surface properties. The addition of maleic anhydride-grafted hydrogenated styrene-based elastomers ensures good compatibility as the hydrogenated styrene portion shares the same structure as the raw material. Furthermore, the maleic anhydride structure can react with other materials such as ABS, PC, or nylon, resulting in a tight bond. The addition of glycidyl methacrylate-grafted olefin copolymer elastomers allows the branched chains to interweave with the randomly distributed side-chain methyl groups of the random copolymer polypropylene, strongly bonding with the material's skeleton. This not only enhances the activity of the maleic anhydride graft but also, due to the highly reactive epoxy groups, allows for ring-opening addition reactions with the end groups of materials like nylon and PC during melting, strengthening adhesion. Additionally, a small amount of thermoplastic polyurethane is added, significantly enhancing the reactivity.

[0006] In one embodiment, the hydrogenated styrene elastomer is at least one of hydrogenated styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-isoprene-styrene triblock copolymer, or hydrogenated styrene-ethylene-isoprene-styrene block copolymer; and has a melt index of 1~10 g / 10 min at 230°C and 2.16 kg.

[0007] Hydrogenated styrene elastomers, when used alone, melt at their physical crosslinking points (PS microregions), causing the material to soften rapidly and lose strength, resulting in poor processability and high cost. Therefore, this application reduces the amount of hydrogenated styrene elastomer used and provides a skeletal structure by incorporating random copolymer polypropylene, thereby increasing processability.

[0008] Therefore, in one embodiment, the ethylene content in the random copolymer polypropylene is 2-10%; the melting point is 145-155℃; and the melt index at 230℃ and 2.16 kg is 1-6 g / 10 min. In the random copolymer polypropylene, ethylene molecules are randomly interspersed among propylene molecules, resulting in a lower melting point and higher melt strength. Adding it to hydrogenated styrene-based elastomers not only serves as a skeletal structure, increasing the material's processability, but also reduces the requirements for subsequent thermal processing, enabling welding with other materials via ultrasonic waves and thermal fusion. Furthermore, it increases the material's transparency and reduces haze, making the material suitable for medical catheters.

[0009] In one embodiment, this application further comprises a glycidyl methacrylate-grafted polyolefin elastomer, wherein the glycidyl methacrylate-grafted polyolefin elastomer is at least one of glycidyl methacrylate-grafted ethylene-1-octene copolymer, ethylene-1-hexene copolymer, and ethylene-1-butene copolymer; the grafting rate is 1.5-3%; the melt index at 230°C and 2.16 kg is 1-10 g / 10 min; and the hardness is 30-50 A. Glycidyl methacrylate grafted polyolefin elastomer has strong compatibility with random copolymer polypropylene in its polyolefin portion. The alkyl groups on each branch interweave to fix the glycidyl methacrylate grafted polyolefin elastomer into the matrix. The epoxy groups of glycidyl methacrylate are highly active and undergo ring-opening addition reactions with the end groups of materials such as nylon and PC during the melting process, thereby enhancing the adhesion.

[0010] In one embodiment, the maleic anhydride-grafted hydrogenated styrene elastomer is at least one of maleic anhydride-grafted hydrogenated styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-isoprene-styrene triblock copolymer, or hydrogenated styrene-ethylene-isoprene-styrene block copolymer; and has a melt index of 5~20 g / 10 min at 230°C and 2.16 kg. Maleic anhydride-grafted hydrogenated styrene elastomers also act as bridges, being compatible with the matrix hydrogenated styrene elastomers. The maleic anhydride, as an active group, can react with other materials such as ABS, PC, or nylon, thereby enhancing the weld strength between materials through chemical bonds and compatibility. Furthermore, glycidyl methacrylate-grafted polyolefin elastomers can further enhance the activity of maleic anhydride-grafted hydrogenated styrene elastomers, further strengthening the bond strength.

[0011] In one embodiment, the thermoplastic polyurethane is a polyester-type thermoplastic polyurethane with a hardness of 60-90A. The polyester-type thermoplastic polyurethane, in synergy with maleic anhydride-grafted hydrogenated styrene elastomers, can achieve "soft and hard overmolding" bonding with random copolymer polypropylene; it enhances the adhesion between random copolymer polypropylene and hydrogenated styrene elastomers, as well as with ABS, PC, or nylon; furthermore, the polyester-type thermoplastic polyurethane can also act as a reaction activator, activating the reactivity of maleic anhydride-grafted hydrogenated styrene elastomers and glycidyl methacrylate-grafted polyolefin elastomers, thus providing better bonding strength. In this embodiment, the amount of thermoplastic polyurethane added is 8%-30% of the mass of the random copolymer polypropylene.

[0012] In one embodiment, the additive is further included, said additive being at least one of antioxidants, slip agents, and modifiers.

[0013] The use of antioxidants and slip agents solves the problems of processing aging and decomposition, as well as the roughness of the finished product surface. The modifier is nano-silica; adding a very small amount of nano-silica improves the surface rigidity, resilience, and ultrasonic welding performance of the material. The nano-silica forms a network-like silica structure in the TPE matrix. This network inhibits material flow and acts as a micro-skeleton, distributing stress more evenly to the bonding interface between TPE and other materials, preventing debonding caused by stress concentration. Furthermore, during bonding with nylon, under ultrasonic or hot-melt conditions, the silica contacts the nylon, inducing a transformation of the nylon crystal form to the more stable α-crystal form; optimizing the surface state of nylon and making its adhesion to TPE stronger. In this embodiment, the average particle size of the silica is 1-100 nm.

[0014] In one embodiment, the antioxidant is 0.1-0.6 parts by weight; the slip agent is 0.01-0.05 parts by weight; and the modifier is 0.2-0.6 parts by weight.

[0015] In one embodiment, the antioxidant is a hindered phenolic antioxidant and / or a phosphite antioxidant; preferably, the hindered phenolic antioxidant is antioxidant 1010, 1076, or 1330; the phosphite antioxidant is antioxidant 168, 618, or 628; when the antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant, the phosphite antioxidant acts as an auxiliary antioxidant, and the mass ratio of the hindered phenolic antioxidant to the phosphite antioxidant is 1:(1-0.5).

[0016] In one embodiment, the slip agent is erucamide and / or oleamide.

[0017] Secondly, embodiments of this application provide a method for preparing a medical TPE material catheter with high ultrasonic welding strength, comprising the following steps: The raw materials are mixed evenly according to the formula ratio, melt-blended, cooled and granulated to obtain a medical TPE material catheter material with high ultrasonic welding strength.

[0018] In one embodiment, the raw materials are mixed in a high-speed mixer at a speed of 1200-1500 rpm; melt blending is carried out in a twin-screw extruder at a melting temperature of 190-210°C.

[0019] Thirdly, embodiments of this application provide the application of the high-strength ultrasonic welding strength medical TPE material catheter material in medical catheters.

[0020] Fourthly, this application provides a medical TPE material catheter, which is prepared by extrusion molding of the above-mentioned high-strength ultrasonic welding strength medical TPE material catheter material at 180~220°C.

[0021] In one embodiment, the medical TPE material catheter is welded to ABS, PC, or nylon material by ultrasound and heating.

[0022] The advantages or beneficial effects of the above technical solutions include at least the following: This application presents a high-strength medical TPE catheter material with high ultrasonic welding strength. It incorporates maleic anhydride-grafted hydrogenated styrene elastomers and glycidyl methacrylate-grafted polyolefin elastomers into random copolymer polypropylene and hydrogenated styrene elastomers, achieving good compatibility with polar materials such as nylon, ABS, and PC. The addition of a small amount of thermoplastic polyurethane significantly enhances the reactivity. Therefore, the material can be welded to ABS, PC, nylon, and other materials without the need for subsequent solvent use via ultrasonic waves and high temperatures, exhibiting excellent weld strength. The preparation process is simple, the raw materials are readily available, and the cost is moderate, demonstrating promising prospects for industrial application. The medical TPE material catheter of this application does not contain plasticizers and meets the safety requirements for medical infusion catheter materials; and it does not require the use of solvents to connect with other components made of materials such as ABS, PC, and nylon, and can achieve excellent welding strength through ultrasound or heating.

[0023] The above overview is for illustrative purposes only and is not intended to be limiting in any way. Further aspects, embodiments, and features of this application will become readily apparent beyond the illustrative aspects, embodiments, and features described above. Detailed Implementation

[0024] In the following description, only certain exemplary embodiments are presented briefly. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of this application.

[0025] The raw materials used in the following embodiments and comparative examples are shown below, and unless otherwise specified, all are commercially available: The random copolymer polypropylene uses an ethylene content of approximately 6%, a melt index of 2.5 g / 10 min (230℃, 2.16 kg); model number R530A; manufactured by Hyosung Corporation, South Korea. The hydrogenated styrene elastomer selected is hydrogenated styrene-butadiene block copolymer (SEBS), with a styrene content of approximately 12% and a melt index of 3.0 g / 10 min (230℃, 2.16 kg); model number G1645; manufactured by Kraton Corporation. The maleic anhydride-grafted hydrogenated styrene elastomer selected is maleic anhydride-grafted SEBS, with a maleic anhydride grafting rate of approximately 1.5% and a melt index of 10 g / 10 min (230℃, 2.16 kg); model number 7131; TSRC Corporation. Glycidyl methacrylate grafted polyolefin elastomer, grafting rate approximately 2.5%, melt index 5 g / 10 min (230℃, 2.16 kg), hardness 42A; model number SOG-03; Shanghai Jiayirong Co., Ltd. The thermoplastic polyurethane selected is a polyester-type thermoplastic polyurethane with a hardness of 80A; model number HF-1180AP; Zhejiang Huafeng Group; The antioxidant is a mixture of antioxidant 1010 and antioxidant 618; The nano-silica particles were selected with a diameter of 40 nm. Oleamide is the preferred slip agent.

[0026] The raw materials for the high-strength ultrasonic welding strength medical TPE catheters in Examples 1-6 are shown in Table 1, and the TPE materials for Comparative Examples 1-7 are shown in Table 2. The preparation methods are as follows: The components of the following formula are mixed evenly in a high-speed mixer at 1200 rpm, melt-blended in a twin-screw extruder at 190~210℃, and then cooled in water, dehydrated, and pelletized to obtain TPE conduit granules. TPE tubing granules are extruded using an extruder at 180~220℃ to obtain sheets of the same thickness.

[0027] The sheet material is then sampled and tested.

[0028] Table 1

[0029] Table 2

[0030] The sample preparation and testing methods are as follows: (1) After the TPE sheet is fully dried, it is pressed into a 1mm thick sheet using a vulcanizing machine. The haze of the material is measured and the results are shown in Table 3.

[0031] (2) After the TPE sheet is fully dried, it is pressed into a 2mm thick sheet using a vulcanizing machine, and then cut into 100mm pieces. A 20mm long strip; after the connector materials (ABS and PC) are thoroughly dried, they are injection molded into 100mm lengths using an injection molding machine. 20mm 5mm sample.

[0032] The TPE material film and the connector material sample are stacked together, with an overlap area of ​​50mm. 20mm. Welding was performed using ultrasonic welding equipment with a frequency of 30kHz, an amplitude of 50%, a gas pressure of 0.2MPa, a welding time of 0.8s, and a holding pressure of 1.0s.

[0033] After welding, the product was placed at room temperature for more than 24 hours before a 180° peel test was performed at a peel speed of 100 mm / min. The product was stretched until the weld separated or the product broke, and the maximum tensile force was recorded. The test was repeated 7 times, and the maximum and minimum values ​​were discarded and the average value was taken. The results are shown in Table 3.

[0034] Table 3

[0035] The maximum peel force of Examples 1-6 is greater than 30N, and the haze is less than 20%. Among them, Example 1 performs best in terms of both maximum peel force and haze performance. Examples 2, 3, and 5 respectively adjusted the three polar polymers: maleic anhydride-grafted hydrogenated styrene elastomer, glycidyl methacrylate-grafted polyolefin elastomer, and TPU. Their maximum peel force is significantly reduced compared to Example 1. Among them, reducing the proportion of thermoplastic polyurethane has the greatest impact on peel force.

[0036] Regarding haze, a suitable ratio among the three is needed to achieve a lower haze value. Examples 3 and 5 are significantly higher than Example 1, while Example 2 is slightly lower than Example 1. Examples 4 and 6 adjusted the ratio of nano-silica, showing that the maximum peel force is positively correlated with the ratio of nano-silica. However, as the ratio of nano-silica increases, the material haze increases, and the extruded conduit becomes hazy and the surface becomes rougher.

[0037] In Comparative Examples 1 to 7, the maximum peel force of Comparative Examples 1 to 3 was less than 30 N. When the ratio of maleic anhydride-grafted hydrogenated styrene elastomer to hydrogenated styrene elastomer was less than 4%; or the ratio of glycidyl methacrylate-grafted polyolefin elastomer to random copolymer polypropylene was less than 20%; or the ratio of thermoplastic polyurethane to random copolymer polypropylene was less than 8%, the weld strength was significantly reduced.

[0038] In Comparative Example 4, the proportion of nano-silica was too low, resulting in a low maximum peel force. In Comparative Example 5, the proportion of nano-silica was too high, leading to excessive haze and substandard product appearance. In Comparative Example 6, the content of thermoplastic polyurethane was too high, resulting in unsatisfactory maximum peel force and haze. In Comparative Example 7, the content of random copolymer polypropylene was too low, significantly reducing the rigidity of the substrate and resulting in a significant decrease in weld strength.

[0039] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of those different embodiments or examples.

[0040] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "a plurality of" means two or more, unless otherwise explicitly specified.

[0041] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any person skilled in the art can easily conceive of various variations or substitutions within the technical scope disclosed in this application, and these should all be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A medical TPE material catheter material with high ultrasonic welding strength, characterized in that, Includes the following components in parts by weight: 15-35 parts of random copolymer polypropylene; 40-60 parts of hydrogenated styrene elastomer; 3-10 parts of maleic anhydride-grafted hydrogenated styrene elastomer; 7-15 parts of glycidyl methacrylate-grafted polyolefin elastomer; 3 to 8 parts of thermoplastic polyurethane.

2. The medical TPE material catheter material with high ultrasonic welding strength according to claim 1, characterized in that, The random copolymer polypropylene contains 2-10% ethylene; its melting point is 145-155℃; and its melt index at 230℃ and 2.16 kg is 1-6 g / 10 min. The hydrogenated styrene elastomer is at least one of hydrogenated styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-isoprene-styrene triblock copolymer, or hydrogenated styrene-ethylene-isoprene-styrene block copolymer; and has a melt index of 1~10 g / 10 min at 230℃ and 2.16 kg. Maleic anhydride-grafted hydrogenated styrene elastomers are at least one of maleic anhydride-grafted hydrogenated styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-isoprene-styrene triblock copolymer, and hydrogenated styrene-ethylene-isoprene-styrene block copolymer; the melt index at 230°C and 2.16 kg is 5~20 g / 10 min. The glycidyl methacrylate-grafted polyolefin elastomer is at least one of glycidyl methacrylate-grafted ethylene-1-octene copolymer, ethylene-1-hexene copolymer, and ethylene-1-butene copolymer; the grafting rate is 1.5-3%; the melt index at 230℃ and 2.16 kg is 1~10 g / 10 min; and the hardness is 30-50 A. The thermoplastic polyurethane is a polyester-type thermoplastic polyurethane with a hardness of 60-90A; the amount of thermoplastic polyurethane added is 8%-30% of the mass of random copolymer polypropylene.

3. The medical TPE material catheter material with high ultrasonic welding strength according to claim 1, characterized in that, It also includes additives, which are at least one of antioxidants, slip agents and modifiers.

4. The medical TPE material catheter material with high ultrasonic welding strength according to claim 3, characterized in that, Antioxidant 0.1-0.6 parts by weight; slip agent 0.01-0.05 parts by weight; modifier 0.2-0.6 parts by weight.

5. The medical TPE material catheter material with high ultrasonic welding strength according to claim 1, characterized in that, The antioxidant is a hindered phenolic antioxidant and / or a phosphite antioxidant; preferably, the hindered phenolic antioxidant is antioxidant 1010, 1076 or 1330; and the phosphite antioxidant is antioxidant 168, 618 or 628. The slip agent is erucamide and / or oleamide; The modifier is nano-silica with an average particle size of 1-100 nm.

6. The method for preparing a medical TPE material catheter with high ultrasonic welding strength according to any one of claims 1-5, characterized in that, Includes the following steps: The raw materials are mixed evenly according to the formula ratio, melt-blended, cooled, and granulated to obtain a medical TPE material catheter material with high ultrasonic welding strength.

7. The method for preparing medical TPE material catheter material with high ultrasonic welding strength according to claim 6, characterized in that, The raw materials are mixed in a high-speed mixer at a speed of 1200-1500 rpm; melt blending is carried out in a twin-screw extruder at a melting temperature of 190-210℃.

8. The application of the high-strength ultrasonic welding strength medical TPE material catheter material as described in any one of claims 1-5 in medical catheters.

9. A medical TPE material catheter, characterized in that, The medical TPE material catheter with high ultrasonic welding strength as described in any one of claims 1-5 is prepared by extrusion molding at 180~220°C.

10. The medical TPE material catheter according to claim 9, characterized in that, The medical TPE material catheter is welded to ABS, PC or nylon materials by ultrasound and heating.